Uso da citometria de fluxo para avaliar os efeitos da alta pressão hidrostática em Saccharomyces cerevisiae - Nati, Tassia (2014)
The main objective of this study was to analyze the high hydrostatic pressure effects in yeast cells by flow cytometry. Saccharomyces cerevisiae Y440 Mat a, leu2 cells had their growth and cell viability assessed by flow cytometry. The cells were subjected to high hydrostatic pressure and their morphological characteristics were analyzed. Changes in cell physiology were observed by using Ethidium Bromide (BE), Bis-oxonol (BOX) and Propidium Iodide (PI). The results show that flow cytometry based on optical data from the light scattering can be used as a relative counting technique, but not as an absolute technique due to the presence of budding cells. SYTO 9 and PI fluorophores were suitable for analyze cell viability, showing strong correlation with the plating technique. High hydrostatic pressure caused cell size and cell complexity reduction